GEOLOGI DAN HIDROGEOLOGI DAERAH BANTARKUNING DAN SEKITARNYA, KECAMATAN CARIU, KABUPATEN BOGOR, JAWA BARAT - Setiadi , Adi
Geological mapping was conducted in Bantarkuning, Bogor Regency, West Java Province, at coordinate 6o32’30”–6o35’00” S and 107o6’00”–107o11’00”E. The objectives of the study were to determine the geological and groundwater quality based on the physical properties of groundwater from springs and dug. The research area is divided into three geomorphology units, namely Pyroclastics Hills of Ciarel Unit, Bantarkuning Folding Hills Unit, and Volcanic and Mountain Unit. The rock units of the study area are divided into five unofficial rock units from old to young, namely the Sandstone-Limestone Unit (Middle Miocene), which is then precipitated laid over it, the Sandstone-Claystone Unit (Miocene End). Then came the igneous rocks of Andesite Lava Unit (Pliocene). Then it is precipitously deposited by the Pyroclastic Breccia Unit (Plistocene). Alluvium is deposited improperly above all exposed units (Recent). Geological structures that developed in the research area are thrust and western-eastern-dominantly oriented folds. Rock units in the research area that acts as aquifer are the Sandstone-Limestone Units, the Sandstone-Claystone Unit, the Pyroclastic Breccia Unit, and the Andesite Lava Unit. The type of aquifer are unconfined aquifer with in sedimentary rock aquifer system and volcanic sediment. The dominant groundwater flow pattern leads to the valley area, to the Cibeet River with groundwater interaction with the river water is effluent. Based on Regulation of the Minister of Health of Republic of Indonesia No.492/MENKES/ PER/IV/2010 regarding drinkable water requirements, 18 of 22 springs and 12 of 71 dug wells are good due to pH values which is less than 6.5. The study area has groundwater with pH 4.46–7.73 and TDS of 10–487 ppm which fall into the category of fresh water.